Ground of degree of trouble stability of grids in the tasks of rise of strength security of flights and efficiency of functioning of airplane - Воробьев, В. М.; Енчев, С. В.; Ищенко, И. М.; Захарченко, В. А. (Problems of Informatization and Control, 2005)
In the article the methods and models rise efficiency functioning the trouble stability systems energy supply, which straight affect strength security of flights, are considered. Efficiency of functioning of grids can be promoted using principle of prevailing for their synthesis. In the tasks of ranging on strength security of flights the model of disrepair with the use of structural-logical method is considered